A Field in Flux : Sixty Years of Industrial Relations - McKersie, Robert B. 1929-; McKersie, Robert B. 1929- (Book collections on Project MUSE., 2019)
"The story of the industrial relations field in America by a man who has been at its center for more than 60 years."